Penerapan Automatic Drip Irrigation System (ADIS) berbasis Internet Of Things (IoT) untuk Monitoring dan Meningkatkan Produktivitas Cabai - Samsu, L.M.; Yahya; Nurhidayati (Infotek: Jurnal Informatika dan Teknologi, 2025)
Padamara Village is one of the villages in Sukamulia District with the largest agricultural expanse reaching 155 Ha, of which 90% is a productive area in the first and second planting seasons after rice. The cayenne pepper plant is a plant that is suitable for cultivation in highland and lowland areas. The optimal growth and yield of cayenne pepper plants is very dependent on adequate soil quality, proper watering management and fertilizer application. Checking soil conditions is very important for the growth of cayenne pepper plants which have optimal humidity of 50%-70% so that they are not too dry or wet with a soil pH of 6-7 and a temperature of 24-28 degrees Celsius. The "SEHATI" farmer group in Padamara Village, Sukamulia District, East Lombok Regency has around 45 farmers with an agricultural land area of ± 15.89 Ha as partners in the Implementation of an Automatic Drip Irrigation System (ADIS) based on the Internet of Things (IoT) for Monitoring and Increasing Productivity Chili in solving problems. Components such as Soil Moisture YL-69 for monitoring soil moisture and pH which will then be sent to the web server for subsequent reading of the results. ESP 32 as a microcontroller to turn on/off the pump water drops.